Resistive Switching: Coexistence of Grain‐Boundaries‐Assisted Bipolar and Threshold Resistive Switching in Multilayer Hexagonal Boron Nitride (Adv. Funct. Mater. 10/2017). (March 2017) - Pan, Chengbin; Ji, Yanfeng; Xiao, Na; Hui, Fei; Tang, Kechao; Guo, Yuzheng; Xie, Xiaoming; Puglisi, Francesco M.; Larcher, Luca; Miranda, Enrique; Jiang, Lanlan; Shi, Yuanyuan; et al.
Abstract : Mario Lanza and co‐workers fabricate resistive random access memories from chemical vapor deposited hexagonal boron nitride in article number 1604811. This two dimensional insulator can be coupled with metallic electrodes, and its conductivity can be tuned via electrical stresses. Penetration of boron ions drives the resistive switching, which is boosted by the generation of boron vacancies, especially at the grain boundaries.